Therapeutic strategies for patients with neuroendocrine neoplasms: current perspectives. Issue 5 (3rd September 2022) - Modica, Roberta; Liccardi, Alessia; Minotta, Roberto; Cannavale, Giuseppe; Benevento, Elio; Colao, Annamaria
ABSTRACT: Introduction: Neuroendocrine neoplasms (NENs) are a heterogeneous group of malignancies mainly arising in the gastroenteropancreatic (GEP) and bronchopulmonary systems, with steadily increasing incidence. The therapeutic landscape has widened and the therapeutic strategy should be based on new sequences and combinations, still debated. Areas covered: Herein, we provide an overview of current approved pharmacological treatments in patients with NENs, with the aim to summarize evidence of efficacy of the main different options in GEP and pulmonary NENs, principally focusing on somatostatin analogs (SSAs), targeted therapy with everolimus and sunitinib, peptide receptor radionuclide therapy (PRRT) and chemotherapy. We discuss biological rationale and toxicities, including current indications according to differentiation and placement in the therapeutic algorithm, clinical trials, and combinations. Furthermore, we recommend areas for further research. Expert opinion: Therapeutic management of patients with NENs represents a challenge for clinicians and the identification of effective sequences and combinations is of utmost importance. Major efforts should be directed to early identify and overcome resistance and to limit toxicity. The progress in the therapeutic management of NENs grows faster and the choice of the best approach should be based on randomized clinical trials, as well as on long-term, real-world data.